2014
DOI: 10.1186/1756-8722-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive transfer of genetically engineered WT1-specific cytotoxic T lymphocytes does not induce renal injury

Abstract: Because WT1 is expressed in leukemia cells, the development of cancer immunotherapy targeting WT1 has been an attractive translational research topic. However, concern of this therapy still remains, since WT1 is abundantly expressed in renal glomerular podocytes. In the present study, we clearly showed that WT1-specific cytotoxic T lymphocytes (CTLs) certainly exerted cytotoxicity against podocytes in vitro; however, they did not damage podocytes in vivo. This might be due to the anatomical localization of pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…8 Moreover, we observed that they exerted cytotoxic effects against podocytes in vitro; however, they did not damage podocytes in vivo. 23 On the basis of these findings, we planned to investigate the safety of the TCR-T cells in this clinical trial, and we did not detect any toxicity to normal tissues. At this time, the major approach to treat acute lymphoblastic leukemia and other B-cell malignancies by antigen-receptor-engineered T cells involves CAR-T cell therapy; in particular, CD19 is the most promising target antigen.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, we observed that they exerted cytotoxic effects against podocytes in vitro; however, they did not damage podocytes in vivo. 23 On the basis of these findings, we planned to investigate the safety of the TCR-T cells in this clinical trial, and we did not detect any toxicity to normal tissues. At this time, the major approach to treat acute lymphoblastic leukemia and other B-cell malignancies by antigen-receptor-engineered T cells involves CAR-T cell therapy; in particular, CD19 is the most promising target antigen.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are concerns about toxicities that may be induced by targeting WT1 expressed in normal tissues with high avidity TCRs. Low levels of expression of WT1 have been found in some normal adult tissues including kidney podocytes (25), CD34+ hematopoetic stem cells (13), and cardiac endothelial cells (42). No toxicities associated with targeting WT1 on normal cells have been reported in vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be due to the recruitment of T cells with low avidity TCRs that survived negative selection in the thymus (22). Some reports have suggested that WT1 reactive T cells can distinguish between tumor cells that overexpress WT1 and normal tissues with lower levels of expression (24, 25). However, caution seems warranted when using a high avidity WT1 reactive TCR since adoptively transferred T cells reactive with epitopes presented on normal tissues, even at very low levels, may induce severe toxicities (5, 9, 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells that are found in IH lesions include hemangioma endothelial cells (HemECs), hemangioma endothelial progenitor cells (HemEPCs), hemangioma stem cells (HemSc) and inflammatory cells [ 17 , 18 , 19 ]. Both HemEPCs and HemSc promote angiogenesis and vasculogenesis, respectively, while inflammatory cells secrete proangiogenic factors such as VEGF [ 20 ]. Thus, these inflammatory cells support neovessel formation.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%